Digital Literacy and Communicative Competence in the New Normal Education - Sapkota, NarayanPrasad (Journal of NELTA Gandaki, 2021)
The COVID -19 pandemic has pushed the education to alternative mode. The New Normal characterized by heavy reliance on technology has been experienced and widely advocated in education. This paper draws on an autoethnographic records which the author collected after the mass initiation of online education in June 2020 until May 2021 to reveal the importance of digital literacy and communicative competence in alternative mode of education in Nepal. The results of study indicate that digital literacy which involves the ability to locate and consume digital content, creating digital content, and communicating digital content needs to be developed further by the primary stakeholders of education. In addition, the study also reveals that the scope of communicative competence increases in alternative mode of education.